Inflammatory Myopathy-Related Interstitial Lung Disease: From Pathophysiology to Treatment - Hervier, Baptiste; Uzunhan, Yurdagül (Frontiers in Medicine, 2020)
Inflammatory myopathies (IM) are auto-immune connective tissue diseases characterized by muscle involvement and by extramuscular manifestations. As such, pulmonary manifestations, which mainly include interstitial lung disease (ILD), often darken two out of four distinct IM, namely dermatomyositis and overlapping myositis. Being the initiation site of the disease and being the leading cause of morbidity and mortality, ILD is of major importance in this context. ILD has a heterogeneous expression among the patients, with various onset mode, various radiological pattern, various severity and finally with different prognoses, which are particularly difficult to predict at the time of IM diagnosis. Therefore, ILD is a challenging issue. Treatments are based on steroids and immunosuppressive or targeted therapies. Their respective place is yet poorly codified however and remains often based on clinician expertise. Dedicated clinical trials are lacking to date and are also difficult to build, due to difficulty of constituting large and homogeneous patient groups and to rigorously evaluate disease outcomes. Indeed, pulmonary function tests alone are being regularly defeated in IM, in which respiratory muscles are often involved. Composite scores, bringing together several lung parameters, should thus be developed and validated in the future, to better assess the disease response to treatment. This review aims to describe the current knowledge of IM immuno-pathogenesis, the clinical features associated with IM related-ILD, focusing of both severity and prognosis, and the actual therapeutic approaches.